1, 3-Bis(1-methyl-1H-tetrazol-5-yl)propane and its coordination polymers with Cu2Cl4 and Cu3Cl6 units. (1st November 2020) - Voitekhovich, Sergei V.; Lyakhov, Alexander S.; Shiman, Dmitriy I.; Grigoriev, Yuri V.; Ivashkevich, Ludmila S.; Klose, Jennifer; Kersting, Berthold; Ivashkevich, Oleg A.
Graphical abstract: Under the action of cupric chloride, a novel bistetrazole shows the N 4, N 4′ -bridging coordination mode, giving 1D coordination polymers with Cu2 Cl4 units. In solution these complexes transform into a 2D coordination polymer, which includes trinuclear Cu3 Cl6 units linked by bistetrazole ligands showing a tridentate N 3, N 4, N 4′ -bridging coordination. Highlights: A novel bistetrazole ligand was prepared by a regioselective procedure. The bistetrazole shows bridging coordination, generating 1D and 2D coordination polymers. In coordination polymers Cu2 Cl4 and Cu3 Cl6 units are linked by bistetrazole. Antiferromagnetic coupling between copper atoms in the Cu3 Cl6 units was observed. Abstract: 1, 3-Bis(1-methyl-1 H -tetrazol-5-yl)propane (bmtp) was prepared by a procedure including regioselective tert -butylation of 1, 3-bis(1 H -tetrazol-5-yl)propane and exhaustive methylation of the obtained 1, 3-bis(2- tert -butyl-1 H -tetrazol-5-yl)propane, followed by removal of the tert -butyl group from the tetrazolium salt under acidic conditions. The ligand bmtp reacts with CuCl2 ·2H2 O in ethanol to give the complexes [Cu3 (bmtp)2 Cl6 (H2 O)2 ] n and [Cu(bmtp)Cl2 ] n . The transformation of [Cu(bmtp)Cl2 ] n into [Cu3 (bmtp)2 Cl6 (H2 O)2 ] n is observed in ethanol. According to single crystal X-ray analysis, [Cu(bmtp)Cl2 ] n was obtained as a mixture of polymorphic forms. They are all 1D coordination polymers, in which polymeric chains include Cu2 Cl4 units linked to each other by two bridging ligands via the tetrazole ring N 4 atoms. [Cu3 (bmtp)2 Cl6 (H2 O)2 ] n presents a 2D coordination polymer, including Cu3 Cl6 units bonded to four others by ligand molecules. In this complex, the tetrazole ligands show monodentate N 4 and bridging N 3, N 4 coordination. The temperature-dependent magnetic susceptibility measurements of this complex revealed that the copper(II) ions are antiferromagnetically coupled, showing a coupling constant J of −4.0 cm −1 .